The Role of Auditor Ethics in Moderating the Effect of Auditor Competence, Independence, and Audit Fees on Audit Quality (Case Study at Malang Public Accounting Firm) - Krisnia, Irna; Rochayatun, Sulis (Jurnal Akuntansi Bisnis, 2024)
As a professional, an auditor has a moral responsibility to the public to provide audit services of highest quality by maintaining integrity, competence and independence in carrying out audit duties. This research aims to examine the role of auditor ethics in moderating the relationship between auditor competence, independence and audit costs and audit quality. A total of 77 respondents were selected from ten Public Accounting Firms in Malang. The research results show that auditor ethics is unable to moderate the relationship between competence, independence and audit fees on audit quality. However, auditor independence and ethics have a direct effect on audit quality. Meanwhile, auditor competency and audit fees have no effect on audit quality. The results of this research can be used as a reference for developing further research related to audit quality and as consideration in formulating policies that can encourage auditors to improve audit quality.